Agencia e Estrutura em Sistemas Internacionais: a ontologia do Realismo Científico e suas implicações para uma agenda de pesquisa | Agency and Structure in International Systems: the ontology of Scientific Realism and its implications for a research agenda - Brancher, Pedro Txai (Mural Internacional, 2019)
O artigo se insere no debate acerca do problema agente-estrutura nas Relações Internacionais.Na primeira seção, analisa-se as controvérsias e as lacunas teóricas de três repostas para o problema agente-estrutura que influenciaram o debate teórico nas RI: individualismo, estruturalismo e estruturação. A segunda seção discute a perspectiva ontológica proposta pelo Realismo Científico. Argumenta-se que ela constitui uma heurística profícua para o desenvolvimento de um programa de pesquisa que conceba agentes e estruturas como entidades autônomas e inter-relacionadas temporalmente. Por fim, nas considerações finais, sintetiza-se os argumentos desenvolvidos, aponta-se implicações teóricas da abordagem sugerida e indica-se alternativas para a continuidade da agenda de pesquisa. ABSTRACT The article is part of the debate on the agent-structure problem in International Relations. It is considered that any social research must develop or incorporate ontological presuppositions about this question, since it logically precedes epistemological and methodological definitions. Specifically to the field of International Relations, the agent-structure problem refers to the definition of the components and the dynamics of operation of International Systems (IS). Thus, in the first section, we analyze the controversies and theoretical gaps of three responses to the agent-structure problem that influenced the theoretical debate in IR: individualism, structuralism and structuring. The second section discusses the ontological perspective proposed by Scientific Realism. It is argued that it constitutes a useful heuristic for the development of a research program that devises agents and structures as autonomous and temporally interrelated entities. Finally, in the final considerations, the arguments developed are summarized, theoretical implications of the suggested approach are indicated, and alternatives are indicated for the continuity of the research agenda. Palavras-chave: Teoria de Relações Internacionais; Agente-Estrutura; Realismo Científico Keywords: International Relations Theory; Agent-Structure; Scientific Realism Recebido em 19 de Dezembro de 2018 | Received on December 19, 2018 Aceito em 31 de Janeiro de 2019 | Accepted on January 31, 2019 DOI: 10.12957/rmi.2018.39008